Melting ice: "Warning Signs" - Malla, Ghana S. (Journal of Agriculture and Environment, 2007)
Melting ice is one of the concerns of world climate scientists and planners. It is the gradual change of ice in the liquid form caused by increase in atmospheric temperature. Global Warming is the increase in atmospheric temperature caused by greenhouse effects (C02, CH4, N20 and CFCs). Increase in temperature of atmosphere by 1oC that has been occurred since 1860 AD (IPCC, 1996). Scientists predicted that the Earth would warm by 1.4 to 5.8oC by 2100. In case of Nepal, increase of temperature was recorded 0.06oC per year (DHM). Sea level rise causes by melting ice is recent warning sign. The Times Center, 2007 estimated sea level rise would be 51 -140 cm by 2100 AD. It affects wide variety of ecosystem, water resources, agriculture, life and livelihoods of people in the world. However, its impact is largely unpredictable and uncertainty. There were series of glacial outburst in Nepal since 1964, destroying ecosystem of surrounding region caused by global warming. Therefore, IPCC member's countries with United State of America (USA) must act quickly to reduce greenhouse gasses to overcome threat of melting ice. The Journal of AGRICULTURE AND ENVIRONMENT Vol. 8, 2007, pp. 66-73